A new approach to streamline obstructive sleep apnea therapy access using peripheral arterial tone-based home sleep test devices - Zou, Ding; Vits, Steven; Egea, Carlos; Ehrsam-Tosi, Daniela; Lavergne, Florent; Azpiazu, Mikel; Fietze, Ingo (Frontiers in Sleep, 2023)
Obstructive sleep apnea (OSA) is a prevalent condition that negatively impacts cardiovascular, metabolic and mental health. A high proportion of individuals with OSA remain undiagnosed and incur significant healthcare costs. The gold standard OSA diagnostic is in-lab polysomnography, but this is costly and time-consuming. Home sleep apnea tests (HSATs), including cardiorespiratory polygraphy and peripheral artery tonometry technology, provide an alternative. Advances in HSAT technology include non-invasive, easy-to-use medical devices that could allow unobtrusive, accessible, multi-night, cost-effective diagnosis and management of sleep-disordered breathing. One type of these devices is based on determination of peripheral artery tone, and use photoplethysmography signals from the finger (oxygen saturation, pulse wave amplitude and pulse rate). The devices contain algorithms that use these data to generate the traditional metrics required by the American Academy of Sleep Medicine. They can be used to record sleep parameters over multiple nights at home, and can also provide information on total sleep time (TST) and sleep stages (including time spent in rapid eye movement sleep). The combination of objective measures (apneahypopnea index, oxygen desaturation index, respiratory disturbance index, TST) and subjective measures (symptoms and other patient-reported outcome measures) could facilitate the development of a personalized therapeutic plan for OSA patients. It is anticipated that the streamlined digital pathway facilitated by new peripheral artery tone-based technology could contribute to reducing the underdiagnosis of OSA, accelerating access to appropriate treatment, and the optimization of OSA therapy.